2000
DOI: 10.1089/thy.2000.10.1035
|View full text |Cite
|
Sign up to set email alerts
|

Novel TSHR Germline Mutation (Met463Val) Masquerading as Graves' Disease in a Large Welsh Kindred with Hyperthyroidism

Abstract: Hereditary nonautoimmune hyperthyroidism is caused by activating germline mutations in the thyrotropin (TSH) receptor (TSHR) gene. We describe an extended Welsh kindred with toxic thyroid hyperplasia affecting 8 family members in three generations and a history consistent with thyrotoxicosis in a further three generations now deceased. A novel heterozygous germline mutation (ATG --> GTG; Met463Val) was identified in the second membrane spanning TSHR region in 6 relatives with thyrotoxicosis and goiter and abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
2
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 26 publications
2
50
2
2
Order By: Relevance
“…Therefore, it is likely that the grandfather might harbor this mutation but showed no history of hyperthyroidism throughout his life. While previous reports showed that nonautoimmune hyperthyroidism was complicated with chronic thyroiditis in several cases [8,14,31], our data indicate that the clinical picture of the affected member 6 was complicated by autoimmune Graves' disease. Constitutively activating TSHR germline mutations have been predominantly identified in TMs but have also been identified in connecting intracellular and extracellular loops (Table 3).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Therefore, it is likely that the grandfather might harbor this mutation but showed no history of hyperthyroidism throughout his life. While previous reports showed that nonautoimmune hyperthyroidism was complicated with chronic thyroiditis in several cases [8,14,31], our data indicate that the clinical picture of the affected member 6 was complicated by autoimmune Graves' disease. Constitutively activating TSHR germline mutations have been predominantly identified in TMs but have also been identified in connecting intracellular and extracellular loops (Table 3).…”
Section: Discussioncontrasting
confidence: 72%
“…Subsequently, 29 germline TSHR mutations in 19 families [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and 10 individuals with sporadic occurrence [19,20] were reported. Clinical characteristics in familial cases include: autosomal dominant transmission, hyperthyroidism with a variable age of onset, hyperplastic goiter of variable size, and absence of clinical or biological features of autoimmunity [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Even among family members harboring the same mutation, clinical features are variable, suggesting that environmental factors including iodine intake, or other genetic factors may be required for full expression of the phenotype.…”
mentioning
confidence: 99%
“…A number of studies have applied a variety of TSHR antibodies in flow cytometry analysis of surface expression of various mutant TSHR, including the mutants examined in the present work (23,24,29,30). The antibodies used have been predominantly BA8 and 3G4/2C11, the former recognises conformation and the latter two a linear epitope in the ECD of the TSHR.…”
Section: Discussionmentioning
confidence: 99%
“…To date, ~30 constitutively activating TSHR mutations have been reported in nonautoimmune hyperthyroidism (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(15)(16)(17)(18)(19). Most of the activating mutations are present in TMD 1, 2, 3, and 5.…”
Section: Discussionmentioning
confidence: 99%
“…Activating germline mutations of TSHR cause nonautoimmune sporadic congenital hyperthyroidism or familial nonautoimmune hyperthyroidism (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). To date, gain-of-function mutations in TMD 1, 2, 3, 5, 6, and 7 and in the ECD have been reported (4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%